The Sacred and the Limits of the Technological Fix - Drengson, Alan R. (Zygon, 1984)
Abstract. Three points are discussed: first, that limits of technological fixes are revealed by current economic, social, and environmental problems; second, that these problems cannot be solved by a technological fix but require alternative forms of activity and being; third, that realizing these limits makes possible the re-emergence of the sacred. Two attitudes toward technology, nature, and the sacred are described: Technocrats desacralize nature and strive to shape it technologically for human ends alone; pernetarians resacralize nature and develop a perennial philosophy (synthesized from elements of different spiritual disciplines) allied with an enlarged, artful science, so as to design activities compatible with nature.